Development of enzymatic pretreatment of palm oil mill effluent for monomers towards biogas production - Tajul Islam, M. S.; Alam, Md. Zahangir; Al-Mamun, Abdullah; Elgharbawy, Amal A.; Riyadi , Fatimah A (Kulliyah of Engineering, International Islamic University Malaysia, 2016)
In anaerobic digestion for enhancement of biogas production, various types of pre-treatment method have been used with some limitations in terms of sustainable environmental management. Although acid and alkali pretreatment have significant effect on the degradation of biomass, these methods have some negative impacts on environment due to their hazardous nature, while the enzymatic pre-treatment is more environmentally friendly. One of the constrains of using enzyme in pretreatment process for biogas production is high cost which is currently focused to reduce cost through using locally produced enzyme. About 66.67% more free fatty acid (FFA) was obtained in this study in compared to control sample by using 12.3 U/ml lipase at the pH of 4.5 with raw POME without sterilized condition. About 34.67% higher reducing sugar was recorded with the loading of 0.168FPU/ml cellulase enzyme as compared to the control at the pH of 3.7